A structural equation model of customer relationship management factors affecting customer retention of long-stay travelers in the thai tourism industry - Tawinunt, K.; Phimonsathienand, T.; Fongsuwan, Wanno (My University, 2015)
Thailand today is projecting nearly 30 million tourist arrivals in 2014 with long-stay tourism a significant and growing component. This study is therefore concerned with the development of a structural equation model for investigating direct and indirect factors associated with customer relationship management and customer satisfaction and the impact on customer retention with long-stay residents and tourists in the domestic Thai travel industry. Data was collected from main tourist areas in from 220 long-staying foreigners. The research found that customer relationship management has a positive impact on customer satisfaction and if an organization has a management system that can respond to tourists needs, the end result will be higher customer loyalty and satisfaction, resulting in higher revenue and long-term profitability. Factors included customer perception of quality and value which had a direct and positive outcome on customer retention. The researchers hope the data will help determine market opportunity strategies while improving management skills while also reducing marketing and operational costs. Better understanding of the needs and buying habits contributes to management strategic planning which strengthens the standards giving the traveler a better feeling of satisfaction. If the consumer is impressed with the service quality, a strong foundation can be established helping with the retention of first-time travelers through word-of-mouth advertising and referrals. As such, Thailand tourism can effectively and efficiently become sustainable and grow its industry for both today and the distant future.
Keywords: Customer relationship management; Customer retention; Customer satisfaction